Walking Molar – A radiographic Presentation - Lakshman, Anusha Rangare; Castelino, Renita Lorina; Balan, Preethi; K.A, Fazil; Kannepady, Sham Kishor (Journal of Medicine and Health Sciences Research, 2021)
Dilaceration is the result of a developmental anomaly in which there has been an abrupt change in the axial inclination between the crown and the root of a tooth. It is seen involving both the permanent and primary dentitions. Root canal curvatures may be apical, gradual, sickle-shaped, severe-moderate-straight curve, bayonet / S-shaped curve and dilacerated curve. Curved root canals exhibit great difficulty in cleaning, shaping and obturation of the root canal system. This mandates routine periapical radiographs which aid the clinician in assessing these morphological variations in the root canal system. This article highlights a rare presentation of dilacerated distal root of left mandibular first molar resembling radiographically as walking molar in 17-year-male patient.